Children’s Experiences of Their Journey to School: Integrating Behaviour Change Frameworks to Inform the Role of the Built Environment in Active School Travel Promotion - Michail, Nafsika; Ozbil, Ayse; Parnell, Rosie; Wilkie, Stephanie (International journal of environmental research and public health, 2021)
Childhood obesity is a public health problem with multiple effects on children’s life. Promoting Active School Travel (AST) could provide an inclusive opportunity for physical activity and shape healthy behaviours. Data for this cross-sectional study were drawn from questionnaires carried out in five primary schools located in Newcastle upon Tyne, UK, in neighbourhoods chosen for their variability in IMD (index of multiple deprivation) and spatial structure of street networks (measured through space syntax measure of integration). A randomly selected and heterogenic sample of 145 pupils (aged 9–10) completed an open-ended questionnaire to state what they like and dislike about their journey to school. Thematic analysis identified four typologies (environmental context, emotions, social influences and trip factors) based on the Theoretical Domains Framework (TDF) and specific themes and sub-themes underlying children’s affective experiences of their journeys to school. This study is the first known to authors to attempt to adapt the Capability, Opportunity and Motivation Behaviour (COM-B) model into AST and children’s experiences and associated behavioural domains with design aspects. Such an insight into children’s attitudes could inform urban planners and designers about how to apply more effective behaviour change interventions, targeting an AST increase among children.